A Phenomenological Study on the Positive and Negative Experiences of Chinese International University Students From Hong Kong Studying in the U.K. and U.S. in the Early Stage of the COVID-19 Pandemic - Lai, Agnes Yuen-kwan; Sit, Shirley Man-man; Lam, Stanley Kam-ki; Choi, Asa Ching-man; Yiu, Denise Yee-shan; Lai, Theresa Tze-kwan; Ip, Mary Sau-man; Lam, Tai-hing (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has caused distress in students globally. The mental health of international students studying abroad has been neglected during the COVID-19 pandemic, especially Chinese students who have been unfairly targeted. Objective: To explore and document the positive and negative experiences of a group of Hong Kong Chinese international students studying in the U.K. and U.S. from an insider perspective in the early stage of the COVID-19 pandemic. Methods: The qualitative study used four 1.5-h online focus group interviews of 20 Chinese international students from Hong Kong aged 18 or older studying in universities in the United Kingdom or the United States, from 3 May to 12 May 2020. A framework approach with a semi-structured interview guide was used to reflect students' stressors, cognitive appraisals, coping, and outcomes (negative impacts and positive gains), in the early stages of COVID-19. Different strategies were used to ensure the credibility, dependability, confirmability, and transferability of the study. Transcripts were analyzed using qualitative thematic content analysis. Results: Twenty full-time international University students (60% female, 90% aged 18–25 years and 65% undergraduates) were recruited. Students reported (i) stress from personal (e.g., worries about health and academic attainment), interpersonal (e.g., perceived prejudice and lack of social support), and environmental factors (e.g., uncertainties about academic programme and unclear COVID-19-related information); (ii) significant differences in culture and cognitive appraisal in the levels of perceived susceptibility and severity; (iii) positive thinking and using alternative measures in meeting challenges, which included effective emotion and problem coping strategies, and the importance of support from family, friends and schools; and (iv) negative psychological impact (e.g., worries and stress) and positive personal growth in crisis management and gains in family relationships. Conclusions: With the rise in sinophobia and uncertain developments of the pandemic, proactive support from government and academic institutions are urgently needed to reduce stress and promote the well-being of international students, especially Chinese students in the U.K. and U.S. Clear information, public education and policies related to the pandemic, appropriate academic arrangements from universities and strong support systems play important roles in maintaining students' psychological health. Clinical Trial Registration: The study was registered with the National Institutes of Health (https://clinicaltrials.gov/, identifier: NCT04365361).